Design, Synthesis, and Biological Evaluation of Triazolyl- and Triazinyl-Quinazolinediones as Potential Antitumor Agents - Abeer N. Al-Romaizan; Nesreen S. Ahmed; Sherin M. Elfeky (Journal of Chemistry)
Novel 6(3-1H-1,2,4-triazol-1-yl)-3-phenylquinazoline-2,4(1H,3H)-diones (7a–e) were synthesized from different enaminones (6a–e) with 6-hydrazinyl-3-phenylquinazoline-2,4(1H,3H)-dione. 2,6(4-2-Substituted-1,3,5-triazin-1(2H)-yl)-3-phenylquinazoline-2,4(1H,3H)-diones (8a–k) were synthesized from the reaction of 1-(2,4-dioxo-3-phenyl-1,2,3,4-tetrahydroquinazolin-6-yl)thiourea, urea, or guanidine (3a–c) with enaminones (6a–e), and a series from 3-substituted-2-imino-1,3,5-triazin-1(2H)-yl-sulfonyl-phenyl-1-methylquinazoline-2,4(1H,3H)-dione (12a–j) were obtained from the reaction of N-(diaminomethylene)-4-(1-methyl-2,4-dioxo-1,2-dihydroquinazolin-3(4H)-yl)benzenesulfonamide (11) with the enaminone (6a–j). The antitumor activity of the synthesized compounds was evaluated against two human cell lines: human colon carcinoma HCT116 and human hepatocellular carcinoma HEP-G2. Some of the tested compounds showed significant potency compared to the reference drug staurosporin.